Dual Energy CT – a Novel Technique for Diagnostic Testing of Fragility Fractures of the Pelvis - Hackenbroch, Carsten; Riesner, Hans-Joachim; Lang, Patricia; Stuby, Fabian; Danz, Burkhardt; Friemert, Benedikt; Palm, Hans-Georg; AG Becken III der Deutschen Gesellschaft für Unfallchirurgie (Zeitschrift für Orthopädie und Unfallchirurgie, 2017)
Background The incidence of fragility fractures of the pelvis is increasing. Established methods to diagnose this condition include X-rays, computed tomography (CT) and magnetic resonance imaging (MRI). Dual energy CT (DECT) is a modern technology for the imaging of bone oedema/bruises and has been used in injuries of the extremities and spine. It is unclear whether this technique can also be used in fragility fractures of the pelvis. The aim of this study was to perform a literature research and survey of the “AG Becken III” members of the German Society of Trauma Surgery (DGU) on the usefulness of DECT in fractures of the pelvis.Material and Methods A PubMed-based literature search on DECT comprised the key words “Dual Energy CT”, “Pelvis/Pelvic”, “Insufficiency” and “Fractures” and their combinations. Thirty-two publications were reviewed completely (full text). Finally, 15 articles were chosen and included in the current study. The survey of the members of the “AG Becken III” was based on a questionnaire and aimed to determine the popularity and potential benefits of DECT in comparison to established diagnostic options.Results No studies on the use of DECT in fragility fractures of the pelvis were identified; the few articles found referred to fractures of the extremities and spine. The response rate to the questionnaire was 25/83 (30.1 %). The participants had a mean personal experience of 8.4 years/151.6 interventions in pelvic surgery. Although some respondents had heard of DECT, this technique – if available – was only used in other indications. However, the potential benefit of DECT was recognised, especially in the acute diagnostic testing of fragility fractures. There is limited consensus on the optimal diagnostic test (CT vs. MRI) of pelvic fractures.Conclusion Although DECT is already established for other indications and is regarded as a promising method by all respondents of the “AG Becken III”, DECT is not yet routinely used for diagnostic testing of fragility fractures of the pelvis. Potential advantages of DECT include its greater sensitivity than CT in detecting bone oedema with equal radiation exposure. Unlike MRI, it is available 24 hours/7 days.Hintergrund Etablierte Verfahren zur Diagnostik von Insuffizienzfrakturen des Beckens sind v. a. CT und MRT, wobei es gerade bei der MRT auf die Darstellung des Knochenmarködems ankommt. Ein modernes Verfahren zur Darstellung von Knochenmarködemen ist die Dual-Energy-CT (DECT). Unklar ist, ob diese Technik auch bei Insuffizienzfrakturen des Beckens anwendbar ist. Ziel unserer Arbeit war es daher, eine Literaturrecherche und Expertenbefragung der AG Becken III der Deutschen Gesellschaft für Unfallchirurgie (DGU) zur Bedeutung der DECT bei Beckenringfrakturen durchzuführen.Material und Methoden Die PubMed-basierte Literaturrecherche umfasste die Suchbegriffe „Dual Energy CT“, „Pelvis“, „Pelvic“, „Insufficiency“ und „Fractures“. Hiervon wurden 32 Publikationen im Volltext durchgesehen und 15 für die aktuelle Arbeit berücksichtigt. Die Befragung der AG Becken III anhand eines Fragebogens zielte auf den Bekanntheitsgrad und potenziellen Nutzen der DECT – auch im Vergleich zu den etablierten diagnostischen Optionen – ab.Ergebnisse In der Literatur lässt sich zur DECT bei Insuffizienzfrakturen des Beckens keine Studie recherchieren; die wenigen gefundenen Arbeiten beziehen sich auf Wirbelkörper- und Extremitätenfrakturen. Die Rücklaufquote der Fragebögen lag bei 25/83 (30,1 %). Die Teilnehmer gaben eine persönliche Erfahrung im Mittel von 8,4 Jahren/151,6 Beckeneingriffen an. Zwar war die DECT teilweise bekannt, die Technik wird – sofern verfügbar – bislang v. a. aber bei anderen Indikationen eingesetzt. Ein Nutzen der DECT wird v. a. in der Akutdiagnostik von Insuffizienzfrakturen gesehen, bei der sich ohnehin nur bedingt ein Konsensus zur bevorzugten etablierten Diagnostik (CT vs. MRT) finden ließ.Schlussfolgerung Obwohl die DECT bei anderen Indikationen bereits etabliert ist und seitens der AG Becken III als aussichtsreiches Verfahren erscheint, so findet diese bislang keinen regelhaften Einsatz bei der Diagnostik von Insuffizienzfrakturen des Beckens. Ihren Vorteil sehen wir v. a. in der höheren Sensitivität durch die Diagnostik von Knochenmarködemen bei gleicher Strahlenbelastung im Vergleich zur klassischen CT sowie in ihrer 24-stündigen Verfügbarkeit im Vergleich zur MRT.
Keywords: dual energy CT; fragility fracture; pelvis